Efektivitas Project Based Learning melalui Desain Poster untuk Meningkatkan Pemahaman Kalimat Majemuk Setara di Sekolah Dasar - Febrilia Dian Novitasari; Nita Kristina; Yeni Setyawan (Universitas Muria Kudus, 2025)
This study examines the effectiveness of implementing Project Based Learning (PjBL) through poster design activities to improve fifth-grade elementary school students’ learning outcomes on compound equal sentences in Indonesian language instruction. PjBL was selected for its student-centered orientation, which emphasizes active participation, collaboration, and the creation of meaningful products as part of the learning process. Mastery of compound-equal sentences is often challenging for elementary students because it requires an understanding of syntactic equivalence, clause relationships, and appropriate connectors within complex sentence structures. This study introduces poster design as a project medium that integrates grammatical understanding with visual literacy and authentic communication tasks. The research employed a qualitative descriptive approach using a case study design. Data were collected through classroom observations, semi-structured interviews with teachers and students, and document analysis of student-created posters. Analysis focused on identifying patterns related to student engagement, understanding of compound-equal sentence structures, collaboration, and learning motivation. The findings reveal a clear improvement in students’ understanding and application of compound-equal sentences, as evidenced by the accuracy and contextual relevance of sentences presented in their posters. Increased student engagement and motivation were also observed, supported by active group discussions, collaborative problem-solving, and sustained participation throughout the project stages. The poster design activity enabled hands-on learning experiences that encouraged critical and creative thinking while fostering social interaction and responsibility within groups. These results demonstrate the practical value of PjBL in transforming abstract grammatical concepts into meaningful learning experiences. The study highlights the potential of PjBL to be adapted and scaled in similar elementary language learning contexts. Future research may explore its application across different language topics, grade levels, or through mixed-method designs to examine long-term impacts on students’ literacy development.